2021
DOI: 10.1108/bepam-06-2020-0108
|View full text |Cite
|
Sign up to set email alerts
|

Investment appraisal and financial benefits of corporate green buildings: a developing economy case study

Abstract: PurposeThis case study aims to appraise the financial benefits of green building construction in developing countries. The case study presents, green building's positive net present value (NPV) investment in real terms and potentially enhanced stock market returns at the firm level compared to competitors.Design/methodology/approachThe case study examines secondary data on a green building certification and longitudinal operation costs to estimate green building investments' financial benefits. The case study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The findings also indicate that the perceptions of construction professionals regarding the most significant value-adding GBFs are on par. This result implies that there is a likelihood of increased effect of green features on green building value such as enhanced environmental performance, improved living quality of occupants, overall maintenance cost and most importantly, the decrease in greenhouse gas emissions and societal benefit (Mesthrige and Kwong, 2018; Verma et al , 2021). The seven components and the features associated with them may be useful in making sound business or economic cases to influence stakeholder’s decision to adopt green buildings in South Africa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings also indicate that the perceptions of construction professionals regarding the most significant value-adding GBFs are on par. This result implies that there is a likelihood of increased effect of green features on green building value such as enhanced environmental performance, improved living quality of occupants, overall maintenance cost and most importantly, the decrease in greenhouse gas emissions and societal benefit (Mesthrige and Kwong, 2018; Verma et al , 2021). The seven components and the features associated with them may be useful in making sound business or economic cases to influence stakeholder’s decision to adopt green buildings in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…maintenance cost). According to Verma et al (2021), the reduction in the use of natural resources also enhance environmental performance and offers societal benefit. Similarly, a report compiled by Dodge Data and Analytics (2018) revealed that the reasons for and benefits attained by applying GBFs include enhanced occupant health because of improved IEQ and healthier living space, energy savings and greater long-term cost savings/profits and most importantly the decrease in greenhouse gas emissions, and hence, the impact of buildings on the environment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In an era where sustainability and environmental responsibility are increasingly becoming a significant concern, green investment has become essential in promoting sustainable development. This framework provides a structural basis for measuring the environmental impact of investments, considering not only the potential financial returns but also the longterm implications for ecosystems and society (Metzger & Schinas, 2019;Verma et al, 2021). The Green Investment Assessment Framework is essential for several reasons that are very relevant in the current economic and environmental context, namely as follows: a.…”
Section: Green Investment Assessment Frameworkmentioning
confidence: 99%
“…To circumvent this problem, awareness and promotion efforts for GB adoption have expanded dramatically. However, in developing countries, the construction sector is still behind (Verma et al, 2021) due to conservative attitudes and a lack of facilitators in place to stimulate GB adoption. While facilitators such as incentives have been recognised as opportunities to advance GB development (e.g.…”
Section: Introductionmentioning
confidence: 99%